Implementation research logic model in the design and execution of eHealth innovations for maternal and newborn healthcare in Ethiopia - Dabere Nigatu; Muluken Azage; Eyaya Misgan; Daniel A. Enquobahrie; Tegegn Kebebaw; Enyew Abate; Esubalew Alemneh; Mirkuzie Woldie; Tsinuel Girma (Health Research Policy and Systems)
Abstract Background The use of eHealth innovations is becoming increasingly important in improving health outcomes, especially for maternal and newborn health. However, planning and executing these innovations can be challenging due to their complex nature. To provide guidance and clarity on implementation approaches, researchers need to use implementation research (IR) tools. We conducted IR to recognize the challenges in implementing eHealth innovations in the context of maternal and newborn healthcare using the implementation research logic model (IRLM). Therefore, this paper aims to describe the practical application of IRLM to design, execute and evaluate eHealth innovations that improve maternal and newborn care in public facilities in Ethiopia. Methods We employed rapid review, formative assessment and process evaluation of an eHealth innovation in selected healthcare facilities serving maternal and newborn care. The eHealth innovation we developed and deployed was named ‘ADHERE’ (Antenatal Care, ChilDbirtH CarE and Postnatal CaRE), representing the continuum of maternal care. The rapid review was conducted as an initial step using the Consolidated Framework for Implementation Research (CFIR). We employed a mix of data collection methods: interview/discussion, eHealth system or document review and direct observation. Furthermore, we executed various stakeholder engagement activities: two co-creation workshops and on-site iterative discussions. We applied the Framework for Reporting Adaptations and Modifications to Evidence-based Implementation Strategies (FRAME-IS) to capture ongoing implementation learnings. Results We developed IRLM of the eHealth innovation implementation for three contexts: urban, peri-urban and remote public healthcare facilities. The model depicted the mechanism of interaction between implementation determinants and implementation strategies to produce the intended implementation outcomes. The IRLM helped to identify more than 35 implementation barriers or facilitators for eHealth interventions and to develop over 17 mitigation strategies for the study contexts. The initial IRLM was refined through ongoing implementation learnings and the mitigation strategies that were executed. Conclusions The IRLM is a comprehensive and effective guiding tool for the development, implementation and evaluation of innovations in various low- and middle-income contexts. Researchers and implementing partners should adapt and use it.